1976
DOI: 10.1002/j.1537-2197.1976.tb13186.x
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretation of Dose‐response Curves for Light‐induced Cell Elongation in Fern Protonemata

Abstract: Protonemata of Onoclea sensibilis and Diyopteris filix‐mas elongate in response to both red and far‐red light. The promotion caused by far‐red is larger than that caused by red light. This phenomenon differs from a typical response to phytochrome, the photoreceptor pigment immediately suggested by the activity of red and far‐red light. The phenomenon has been explained by two different hypotheses, one of which holds that phytochrome is solely responsible for the response, whereas the other postulates an intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…The general shapes of the quantum dose-A filament length curves for 560, 660, and 720 nm irradiation (Fig. 4,6,8) bear close resemblance to the shapes of published curves (Greany and Miller, 1976). The only important difference is that those authors observed that high doses of 660-nm light elicit a stable optimal response, whereas Fig.…”
Section: Results-supporting
confidence: 59%
See 1 more Smart Citation
“…The general shapes of the quantum dose-A filament length curves for 560, 660, and 720 nm irradiation (Fig. 4,6,8) bear close resemblance to the shapes of published curves (Greany and Miller, 1976). The only important difference is that those authors observed that high doses of 660-nm light elicit a stable optimal response, whereas Fig.…”
Section: Results-supporting
confidence: 59%
“…Intensity measurements were performed periodically in the course of experimentation to confirm that the output of the light source had remained constant. It has been reported that the photoresponses of filamentous gametophytes exhibit dose-response reciprocity within the range of the quantum doses of the wavelengths employed in this study (Miller and Miller, 1967a;Greany and Miller, 1976).…”
mentioning
confidence: 54%
“…These results do not implicate phytochrome as the primary photoreceptor in red light-induced filament elongation in this species. Despite the fact that blue light is generally implicated in planar growth, form change in the gametophytes of O. sensibilis is also induced by high intensity red light (Greany and Miller, 1976), while short periods of blue light induce filamentous growth (Miller and Miller, 1964). Although there is no evidence for a "light intensity factor" in the present experiments, one cannot completely eliminate the possibility of a photosynthetic rather than a photomorphogenetic effect oflight in this system.…”
Section: Discussioncontrasting
confidence: 61%
“…However, this obligate dependence on the blue light receptor does not seem characteristic of all gametophytes. Red light of moderate to high intensity will cause the morphological transition in filaments of Alsophila australis (Mohr and Barth, 1962), Pteris vittata and Osmunda japonica (Kato, 1968), Lygodium japonicum (Raghavan, 1973), and Onoclea sensibilis (Greany and Miller, 1976). These red-lightmediated transitions in growth form argue against Ohlenroth and concept that blue light acts as a specific trigger that induces/derepresses the gene constellation for two-dimensional growth.…”
Section: Ame~canjournalofbotanymentioning
confidence: 99%